Pengaruh Lingkungan Kerja dan Motivasi terhadap Kinerja Karyawan melalui Employee Engagement sebagai Variabel Intervening pada PT Tri Bahtera Srikandi - Putri Azizi; Achmad Rendi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study aims to analyze the influence of the work environment and work motivation on employee performance through employee engagement as an intervening variable at PT Tri Bahtera Srikandi. The problem underlying this research is the suboptimal employee performance, as indicated by the company's production realization that has not yet met the established targets. This study employed a quantitative approach using a survey method. The population consisted of all employees of PT Tri Bahtera Srikandi, with a sample of 70 respondents selected using a saturated sampling technique. Data were collected through questionnaires and analyzed using the Partial Least Squares (PLS) method with the SmartPLS application. The results of the study indicate that the work environment has a positive and significant effect on employee engagement, with a coefficient value of 0.441 and a p-value of 0.000. Work motivation also has a positive and significant effect on employee engagement, with a coefficient value of 0.454 and a p-value of 0.000. Furthermore, the work environment has a positive and significant effect on employee performance, with a coefficient value of 0.413 and a p-value of 0.000. Work motivation has a positive and significant effect on employee performance, with a coefficient value of 0.285 and a p-value of 0.004. Employee engagement also has a positive and significant effect on employee performance, with a coefficient value of 0.323 and a p-value of 0.000. The findings indicate that employee engagement acts as an intervening variable in the relationship between the work environment and work motivation and employee performance.This study concludes that improving the quality of the work environment, providing appropriate work motivation, and strengthening employee engagement can enhance employee performance at PT Tri Bahtera Srikandi.